Faiths, Fairs and Festivals of India - Buck, C.H. (Brill | Manohar Publishers & Distributors, 2024)
This concise volume on fairs, religions, and festivals teaches about the diverse Indian culture. This book covers the mainstream religions of India - Hinduism, Islam, Buddhism, Jainism, Sikhism, and Zoroastrianism, and also talks about the inhabitants, i.e. Aborigines and Aryans. It also discusses the sacred canons and other literature of the said religions, such as Vedas, Dharmasastras, Jatakas, Quran, and Zend Avesta, etc. However the main part of this book deals with sacred festivals celebrated in India, prevailing belief systems, sects, societies, marriage practices, saints, superstitions, and fairs associated. The book will be of interest to both general and academic readers.